Challenges to Nursing Values in a Changing Nursing Environment - Gastmans, Chris (Nursing ethics, 1998)
The aim of this paper is to analyse how the broad context of nursing practice plays a stimulating and/or a restricting role in the process of ethical caring. Three areas of special attention are noted. First, on the societal level, some developments that influence the state of affairs in the caring sector are indicated. Secondly, concerning the nursing and medical professions, an interprofessional dialogue based on specific competence is outlined. Thirdly, there is a discussion of how health care institutions can evolve from a business undertaking to a pedagogic-moral area where nurses can learn the moral attitudes that are essential to achieve ‘good care’.